Functional analyses of the primate upper cervical vertebral column. Issue 107 (June 2017) - Nalley, Thierra K.; Grider-Potter, Neysa
Abstract: Recent work has highlighted functional correlations between direct measures of head and neck posture and primate cervical bony morphology. Primates with more horizontal necks exhibit middle and lower cervical vertebral features that indicate increased mechanical advantage for deep nuchal musculature and mechanisms for column curvature formation and maintenance. How features of the C1 and C2 reflect quantified measures of posture have yet to be examined. This study incorporates bony morphology from the upper cervical levels from 20 extant primate species in order to investigate further how posture correlates with cervical vertebrae morphology. Results from phylogenetic generalized least-squares analyses indicate that few vertebral features exhibit a significant relationship with posture when accounting for differences in size. When size-adjusted traits were correlated with posture, vertebral variation had a stronger relationship with neck posture than head posture variables. Two C1 traits—relative posterior arch length and superior facet curvature—were correlated with neck posture variables. Relative posterior arch length exhibits a positive relationship with neck posture, while superior articular facet curvature demonstrates a negative relationship, such that as the neck becomes more horizontal, the greater the facet curvature. Four C2 features were also correlated with neck posture: relative pedicle and lamina lengths, relative superior facet orientation, and dens orientation. Relative pedicle and lamina lengths become craniocaudally longer as the neck becomes more horizontal. Relative C2 superior facet orientation and dens orientation exhibit negative correlations with posture, such that as the neck becomes more horizontal, the superior facet becomes more caudally inclined and the dens more dorsally inclined. These results produce a similar functional signal observed in the middle and lower cervical spine. Modeling the cervical vertebrae of more pronograde taxa within a sigmoidal spinal column model is further discussed and may prove useful in refining and testing future hypotheses of primate cervical mechanics.